Life skill program in business and entrepreneurship - Rony Setiawan; Ariesya Aprillia; Ika Gunawan; Surya Setyawan; Ida Ida; Kartika Imasari Tjiptodjojo; Felicia Abednego; Robby Tan (Universitas Muhammadiyah Magelang, 2022)
Universities must take an active role in providing services to their communities, particularly to the youth. The Faculty of Economics at Maranatha Christian University and the Christian Education Agency Penabur collaborated to host an online webinar on a life skills program in business and entrepreneurship. Participants in the program are high school students from Generation Z, who value encouragement, practicality, and financial stability in their time. This program aims to make every participant willing and capable of seeing, knowing, understanding, and being motivated to engage in business and entrepreneurial practices such as personal finance management, small business development, and capital market investing. Distance learning, which is done online and includes interaction and discussion, is the method used. More than 70% of those who took part in the three-day virtual learning activities expressed positive attitudes and intentions. They are commonly very enthusiastic about attending future webinars on investment, business, and entrepreneurship.